- Analisis Ketepatan Kode Diagnosa Pada Kasus Persalinan Dengan Sectio Caessarea Di RSUD Sleman Yogyakarta: - - Rina Yulida; Harinto Nur Seha; Hikmah Mau’idzoh Khafi (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2021)
Abstract Background: disease classification coding system is a grouping of diseases into one group with the same disease code number according to the ICD-10. Purpose: Knowing the accuracy of the eye and adnexa diagnosis code based on ICD-10 at PKU Muhammadiyah Hospital Yogyakarta. Methode: This research uses descriptive research with a qualitative approach. This research was conducted at PKU Muhammadiyah Hospital Yogyakarta. The sampling technique used is Systematic Random Sampling. The total population used was 46 inpatient medical record documents and 3 respondents. Results: The coding of diagnoses at PKU Muhammadiyah Hospital Yogyakarta was carried out by 7 coding officers with educational qualifications of D3 Record Meids. The accuracy of the eye and adnexa diagnosis code at PKU Muhammadiyah Hospital Yogyakarta is (74%) while the incorrect diagnosis code is (26%). Coding inaccuracy factors are due to incomplete medical record files and coding officers who have difficulty reading the doctor's writings. Conclusion: The coding accuracy reached (74%) while the diagnosis code was incorrect (26%). Coding inaccuracy factors are due to incomplete medical record files and coding officers who have difficulty reading the doctor's writings. Suggestion: The percentage level of incompleteness in the medical record file, especially on the summary sheet of Incoming Out and Medical Resume needs to be increased in order to improve the quality of better service Keywords: Medical Records, Accuracy of Eye and Adnexa Codification, ICD-10.